2019
DOI: 10.33549/physiolres.934383
|View full text |Cite
|
Sign up to set email alerts
|

Elevated age-related cortical iron, ferritin and amyloid plaques in APPswe/PS1ΔE9 transgenic mouse model of Alzheimer’s disease

Abstract: Iron is very important element for functioning of the brain. Its concentration changes with aging the brain or during disease. The aim of our work was the histological examination of content of ferritin and free iron (unbound) in brain cortex in association with Aβ plaques from their earliest stages of accumulation in amyloid plaque forming APP/PS1 transgenic mice. Light microscopy revealed the onset of plaques formation at 8-monthage. Detectable traces of free iron and no ferritin were found around plaques at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…In particular, Aβ plaques found in the AD cortex and hippocampi are associated with iron deposits and ferritin [37][38][39]. In accordance with previous studies of AD model mice [40][41][42], we demonstrated significant increases of ferritin in the cortex of 7-month-old 5xFAD mice. Since ferritin is responsible for attenuation and sequestration of free iron [43], ADassociated increases of ferritin levels may indicate elevated labile iron level in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, Aβ plaques found in the AD cortex and hippocampi are associated with iron deposits and ferritin [37][38][39]. In accordance with previous studies of AD model mice [40][41][42], we demonstrated significant increases of ferritin in the cortex of 7-month-old 5xFAD mice. Since ferritin is responsible for attenuation and sequestration of free iron [43], ADassociated increases of ferritin levels may indicate elevated labile iron level in the brain.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, aging and changes in iron metabolism are associated with the development of Aβ plaques and NFTs. Svobodová et al [ 142 ] demonstrated in an APP/PS1 transgenic mice model that free iron and ferritin accumulation follows amyloid plaque formation in the cerebral cortex area. In fact, iron deposition has been involved in the misfolding process of the Aβ plaques and NFTs [ 143 ].…”
Section: Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore, aging and changes in iron metabolism are associated with the development of Aβ plaques and NFTs. Svobodová et al [142] demonstrated in an APP/PS1 transgenic mice model that free iron and ferritin accumulation follows amyloid plaque formation in Alzheimer's disease. The development and progression of Alzheimer's disease (AD) lead to atrophy, loss and dysfunction of both neurons and glial cells.…”
Section: Ferroptosis In Alzheimer's Diseasementioning
confidence: 99%
“…By lysing A␤ plaques, which in AD are overloaded with iron, P. gingivalis probably achieves access to iron either as heme, free iron or ferritin (one of the intracellular iron-storage proteins of P. gingivalis). Ferritin accumulates mainly at the edge of A␤ plaques, while a smaller amount of free iron is observed in the plaque-free tissue, as well as in and around A␤ plaques [24]. Whether P. gingivalis (1) lyses plaques through their gingipains, (2) acquires iron in the plaque surroundings, (3) extracts iron from plaque-free brain tissue, or (4) takes it from ferritin or microglia, the consequences of acquisition of iron from these sources may aggravate the iron dyshomeostasis existing in the AD brain.…”
Section: Porphyromonas Gingivalis May Seek the Brain To Acquire Hemementioning
confidence: 97%
“…Detectable traces of free iron, but no ferritin, were seen around plaques at this age, while their accumulation in and around A␤ plaques had increased at 13 months. Ferritin accumulated mainly at the edge of A␤ plaques, while a smaller amount of free iron was observed in the plaque-free tissue, as well as in and around A␤ plaques [24]. Secreted ferritin, which reflects the intracellular iron load, was increased in the cerebrospinal fluid of individuals with mild cognitive impairment and may be used to predict a near-term progression risk of the disease [2].…”
Section: Dysregulated Iron Homeostasis and Alzheimer's Diseasementioning
confidence: 99%